2014
DOI: 10.1016/j.apal.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The axiomatic power of Kolmogorov complexity

Abstract: A preliminary version of this paper was presented on a special session of the Computability in Europe conference (CiE), June 2012.International audienceThe famous Gödel incompleteness theorem states that for every consistent sufficiently rich formal theory T there exist true state- ments that are unprovable in T. Such statements would be natural can- didates for being added as axioms, but how can we obtain them? One classical (and well studied) approach is to add to some theory T an axiom that claims the consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Theorem 4 (Solovay (1975)). ( ) = ( )+ (2) ( )± ( (3) ( )), and this result is tight in that we cannot extend it to (4)…”
Section: Definitionmentioning
confidence: 90%
See 2 more Smart Citations
“…Theorem 4 (Solovay (1975)). ( ) = ( )+ (2) ( )± ( (3) ( )), and this result is tight in that we cannot extend it to (4)…”
Section: Definitionmentioning
confidence: 90%
“…3 Other recent work has explored the effect of adding axioms asserting the incompressibility of certain strings in a probabilistic way. Bienvenu, Romashchenko, Shen, Taveneaux, and Vermeeren [4] have shown that this kind of procedure does not help to prove new interesting theorems, but that the situation changes if we take into account the sizes of the proofs: randomly chosen axioms (in a sense made precise in their paper) can help to make proofs much shorter under the reasonable complexity-theoretic assumption that NP ≠ PSPACE.…”
Section: Some Interactions With Computabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given a string x of complexity n, and some m < n, we can study the axiomatic power of the statement C(x) > m, in particular, the complexity of the universal statements that follow from it. (Universal statements are statements about non-termination of some program in an optimal programming language, and their complexity is the length of this program, see [12] for details.) If x and x ′ have small information distance, then we can positively check this, and therefore the high complexity of x provably implies (almost as) high complexity of x ′ and vice versa.…”
Section: Information-theoretic Propertiesmentioning
confidence: 99%